EVALUATION OF ANTI-OXIDANT AND ANTI-BACTERIAL FUNCTIONALITIES OF COMMON CARP (CYPRINUS CARPIO) ENZYMIC ELASTIN HYDROLYSATE - Kadhim, A. M; Shakir, K. A (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was amid to assess the radical scavenging activity, reducing power and total antioxidant capacity of elastin enzymatic hydrolysate (EEH) which prepared by treating common carp bulbus elastin extract with elastase for 10 hours at 40 C°. Aliquots of reaction solution were taken every 2 hours to point out the optimum degree of hydrolysis based on the highest antioxidant value. The hydrolysate which obtained after 8 hours hydrolysis was chosen to be evaluated for improving minced beef meat shelf-life based on the bacterial contents and lipid oxidation under refrigerated storage (4 C°/ 10 days). This study included 6 groups: group C without EEH addition, groups EEH1, EEH2 and EEH3 with 50, 100 and 150 mg EEH/ 100 gm meat, in addition to group A (100 mg ascorbic acid/ 100 gm meat) and group B (100 ppm of BHT) for comparison. The antioxidant activity of elastin hydrolysate was proportional to the time of hydrolysis, where the highest radical scavenging activity (RSA) and total antioxidant capacity (TAC) were achieved after eight hours of hydrolysis (21.44 % and 205.41 mg equivalent ASC/ 100 ml respectively). While the highest value for reducing power test was after ten hours of hydrolysis (0.422 nm). The results indicate that the concentration of elastin hydrolysate was an effective factor in reducing the peroxide value (PV), Thiobarbituric acid (TBA) and total volatile nitrogen (TVN) during storage period. Meanwhile, the pH value was increased with increasing the concentration of elastin hydrolysate, while the free fatty acid (FFA) values varied during storage when the EEH3 group was recorded the least FFA value. The bacterial contents of minced meat were declined with increasing the concentration of EEH, where EEH3 group recorded the lowest count of TPC, S. aureus and Salmonella as compared to A, B and C groups. In conclusion, the fish enzymatic elastin hydrolysate is a promising natural antioxidant/ antibacterial as a good alternative for synthetic compound.